138k views
1 vote
When a polynomial is divided by (x+2), the remainder is -19. When the same polynomial is divided by (x-1), the remainder is 2. Determine the remainder when the polynomial is divided by (x-1)(x+2).

1 Answer

4 votes

Answer: 7x - 5

============================================

Step-by-step explanation:

We're dividing some unknown polynomial P(x) over (x+2) to get a quotient Q1(x) and remainder -19. That must mean

P(x)/(x+2) = Q1(x) - 19/(x+2)

P(x) = Q1(x)*(x+2) - 19

Note that plugging in x = -2 leads to P(-2) = -19. This is an example of the remainder theorem.

Similarly,

P(x) = Q2(x)*(x-1) + 2

since dividing by (x-1) leads to a remainder of 2. We have P(1) = 2.

We'll use P(-2) = -19 and P(1) = 2 in the later sections below.

----------------

We want to find the value of r such that

P(x) = Q3*(x+2)(x-1) + r

Let's say that r = ax+b

Meaning we now have

P(x) = Q3*(x+2)(x-1) + r

P(x) = Q3*(x+2)(x-1) + ax+b

The goal from here is to find 'a' and b so we can get the remainder ax+b.

----------------

Plug in x = -2 and solve for b.

P(x) = Q3*(x+2)(x-1) + ax+b

P(-2) = Q3*(-2+2)(-2-1) + a(-2)+b

-19 = Q3*(0)(-3)-2a+b

-19 = -2a+b

b = 2a-19

----------------

Plug in x = 1 to get...

P(x) = Q3*(x+2)(x-1) + ax+b

P(1) = Q3*(1+2)(1-1) + a(1)+b

P(1) = a+b

2 = a+b

a+b = 2

a+(2a-19) = 2 .... plug in b = 2a-19

3a-19 = 2

3a = 19+2

3a = 21

a = 21/3

a = 7

Use that value to find b

b = 2a-19

b = 2(7)-19

b = 14-19

b = -5

----------------

We found that a = 7 and b = -5.

The remainder ax+b updates to the final answer 7x-5

User Hiedi
by
5.3k points